DIVIDEND PAYOUT RATIO DAN FAKTOR YANG MEMPENGARUHINYA - Utama, I Made Karya (Manajemen Bisnis Syariah, 2012)
This research is conducted to examine whether the company size, cash ratio, debt to equity ratio, and return on asset affect the dividend payout ratio. The number of samples used in this study is 23 manufacturing companies listed on Indonesia Stock Exchange during the period of 2006-2010 and chosen by using purposive sampling method. Multiple regression analysis is used and to prove the hypothesis, the F test and t test were done by using Statistical Package for Social Sciences (SPSS) for Windows 15.0. The study results show that all independent variables; the company size, Cash Ratio, Debt to Equity Ratio, and Return on Asset simultaneously affect the Dividend Payout Ratio of manufacturing companies chosed as the samples of this study. The adjusted R Square is 0,137. It means that 13,7% variation of Dividend Payout Ratio influenced by the company size, Cash Ratio, Debt to Equity Ratio, and Return on Asset, while the rest of 86,3% influenced by other factors which are not included in the model. The t test shows that only the company size and Cash Ratio partially significant affect Dividend Payout Ratio.  Keywords: Dividend Payout Ratio, Company Size, Cash Ratio, Debt to Equity Ratio, Return on Asset